Advertising, Breadth of Ownership, and Liquidity - Grullon, Gustavo; Kanatas, George; Weston, James P. (Review of Financial Studies, 2004)
We provide empirical evidence that a firm's overall visibility with investors, as measured by its product market advertising, has important consequences for the stock market. Specifically we show that firms with greater advertising expenditures, ceteris paribus, have a larger number of both individual and institutional investors, and better liquidity of their common stock. Our findings are robust to a variety of methodological approaches and to various measures of liquidity. These results suggest that the investors' degree of familiarity with a firm may affect its cost of capital and consequently its value.